Nutritional intervention in patient with severe acute pancreatitis, calculous chronic cholecystitis and diabetes mellitus type 2 - Solís Guevara, Fernando Daniel (2019)
Pancreatitis is inflammation of the pancreas. The severity involves organic failure, local complications and prognostic markers, with severe acute pancreatitis of greater catabolism, which affects the nutritional status. Chronic cholecystitis is inflammation of the gallbladder. In type 2 diabetes, hyperglycemia is caused by insulin resistance and insufficient secretion of this. The case of a 40-year-old male undertaking epigastric pain, nausea and vomiting, whose diagnosis is severe acute pancreatitis corroborated by biochemical and TEM analyses, is presented. Ultrasound denotes the presence of chronic cholecystitis calculus. The Analytical data confirm type 2 diabetes. Patient is improving and tolerating nutritional support, although it is not operated. Early diagnosis and nutritional intervention are vital for patient recovery and avoid complications.